La percepción. El dibujo y la visión. - Araújo, Iván (Arte, Individuo y Sociedad, 2000)
Man analyzes tIte external through the process and abstraction of the perceptual information, beíng te phenomenon of vísion the beginíng of a series of complex operations which will later determine the quality of its representations. Perception confirms itself as an active and selective phenomenon with relation to its ability to stablish organized associations of the discontinuities whieh appear in the visual ficíd. Drawing as a vehicle of form analysis nceds vision to stablish that indispensable connection with the external. Thc type of image as a formal synthesis determines itself as a peculiar way of seeing the external, forcing te one who draws to make a selection and to synthesize the perceptual material by complex operations of abstraction leading to generate te image.
Keywords: drawing; perception; víslon; form; Klee; Amheim; object; abstraction; representation